(untitled) (Global Journal of Management and Business Research, 2020)
The study assesses the impact of monetary policy on Vietnamese commercial banks’ insolvency risk during the 2008-2017 period, with balanced panel data for 30 commercial banks in Vietnam. Results from the study show that an increase in the M2 money supply creates an increase in the Z index, which means a reduction in the risk of insolvency. The expansionary monetary policy increases real estate prices, collateral value, and bank capital, resulting in higher asset value for the bank. As a result, both deposit growth and credit growth in the economy have positive signs; therefore, the activity of commercial banks results in efficiency and improved profit, reducing the risk of insolvency. This result is consistent with the Borio and Zhu (2012) reports.